Direct Oxidation of Benzene to Phenol in Liquid Phase over Nanoporous Silica of Chromium-LUS-1 - Ghodsi Mohammadi Ziarani; Mehrdad Manteghian; Alireza Abbasi; Alireza Badiei; Javad Gholami (Iranica Journal of Energy and Environment, 2013)
Direct oxidation of benzene to phenol in liquid phase in the medium of methanol, acetone, acetic acid and acetonitrile as a solvent over chromium catalyst supported on highly ordered nanoporous silica (Cr-LUS-1) by H2O2 were examined. The best results obtained from methanol solvent with 20% yield and selectivity of 90%. Cr-LUS-1 characterized by XRD, nitrogen adsorption-desorption isotherms and visible spectrophotometer.